Knowledge atlas of the involvement of glutamate and GABA in alcohol use disorder: A bibliometric and scientometric analysis - Wang, Zhanzhang; Zhu, Xiuqing; Ni, Xiaojia; Wen, Yuguan; Shang, Dewei (Frontiers in Psychiatry, 2022)
Introduction: Abnormal neurotransmission of glutamate and γ-aminobutyric acid (GABA) is a key characteristic of alcohol-related disorders. To track research output, we conducted a bibliometric analysis to explore the current status and trends in this field over the past decades. Methods: Studies related to neurotransmitters and alcohol use disorder published in English from 2005–2021 were retrieved from the Web of Science Core Collection and Scopus databases. The R–bibliometrix package was used for a descriptive analysis of the publications. Citespace, WOSviewer, and R–bibliometrix were used to construct networks of countries/institutions/authors based on co-authorship, co-citation analysis of cited references and co-occurrence as well as burst detection of keywords. Results: A total of 4250 unique articles and reviews were included in the final analysis. The annual growth rate of publications was 5.4%. The USA was the most productive country in this field, contributing nearly half of the total documents. The top ten most productive institutions were all located in the USA. The most frequent worldwide collaboration was between the USA and Italy. The most productive and influential institution was the University of California. The author contributing the most productions to this field was Marisa Roberto from the Scripps Research Institute. The top co-cited reference was a review titled “Neurocircuitry of addiction”. The top journal in terms of the number of records and citations was Alcoholism: Clinical and Experimental Research. Comprehensive analyses have been conducted over past decades based on co-cited reference analysis, including modulators, transporters, receptor subtypes, and animal models. In recent years, the research frontiers have been shifting to the identification of risk factors/biomarkers, drug development for alcohol use disorder, and mechanisms related to alcoholic and non-alcoholic fatty liver. Conclusion: Our bibliometric analysis shows that glutamate and GABA continue to be of interest in alcohol use disorder. The focus has evolved from mechanisms and medications related to glutamate and GABA in alcohol use disorder, to novel drug development, risk factor/biomarker identification targeting neurotransmitters, and the mechanisms of related diseases.